Genetic investigation of 93 families with microphthalmia or posterior microphthalmos. Issue 6 (25th March 2018) - Patel, N.; Khan, A.O.; Alsahli, S.; Abdel‐Salam, G.; Nowilaty, S.R.; Mansour, A.M.; Nabil, A.; Al‐Owain, M.; Sogati, S.; Salih, M.A.; Kamal, A.M.; Alsharif, H.; et al.
Abstract : Microphthalmia is a developmental eye defect that is highly variable in severity and in its potential for systemic association. Despite the discovery of many disease genes in microphthalmia, at least 50% of patients remain undiagnosed genetically. Here, we describe a cohort of 147 patients (93 families) from our highly consanguineous population with various forms of microphthalmia (including the distinct entity of posterior microphthalmos) that were investigated using a next‐generation sequencing multi‐gene panel (i‐panel) as well as whole exome sequencing and molecular karyotyping. A potentially causal mutation was identified in the majority of the cohort with microphthalmia (61%) and posterior microphthalmos (82%). The identified mutations (55 point mutations, 15 of which are novel) spanned 24 known disease genes, some of which have not or only very rarely been linked to microphthalmia ( PAX6, SLC18A2, DSC3 and CNKSR1 ). Our study has also identified interesting candidate variants in 2 genes that have not been linked to human diseases ( MYO10 and ZNF219 ), which we present here as novel candidates for microphthalmia. In addition to revealing novel phenotypic aspects of microphthalmia, this study expands its allelic and locus heterogeneity and highlights the need for expanded testing of patients with this condition. Abstract :